The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3329/pa.v24i1-2.19116
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Max Yeast Culture Probiotic in Potentiating the Growth Performance of Commercial Broiler

Abstract: The present study is under taken to determine the body weight gain of broilers, to determine carcass yield or dressing percentage of broilers, to determine feed conversion ratio of broilers, to enumerate the colonizing micro flora in the gut of broilers. A total of 80 day-old broiler chicks were divided into two main groups I and II with 40 chicks in each. Group I was supplemented with Probiotic (Max Yeast Culture gm/kg feed) containing feed and chicks of group II was supplemented with conventional feed. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…This study has revealed that papaya leaf and kalo jeera seeds extract had no significant effect on the hematological parameters (Table 4). This findings, however, does not agree with Islam et al (2013a) who reported that bitter principles of medicinal plants possess a strong influence on hematological traits particularly Hb, depending on their nutritional status.…”
Section: Resultscontrasting
confidence: 98%
“…This study has revealed that papaya leaf and kalo jeera seeds extract had no significant effect on the hematological parameters (Table 4). This findings, however, does not agree with Islam et al (2013a) who reported that bitter principles of medicinal plants possess a strong influence on hematological traits particularly Hb, depending on their nutritional status.…”
Section: Resultscontrasting
confidence: 98%
“…Cost-benefit analysis of broiler production by using feed supplemented with tulsi leaf extract from 2-5 weeks of age Supplementation with tulsi extract was more profitable than control group (Table 3) but the difference was not significant (p>0.05). The study has revealed that supplemented with tulsi leaf extract had higher body weight gain, weekly gain in weight, feed consumption and feed efficiency (Islam et al, 2013). These results may be due to antimicrobial and anti-protozoal properties (Kale et al, 2003) of tulsi leaves, which help to reduce the microbial load of birds and improved the feed consumption and feed efficiency of the birds (Pushpagadan and Sobti, 1977).…”
Section: Resultsmentioning
confidence: 88%